Wizerunek organizacji niedochodowych - znaczenia i kreowanie - Iwankiewicz-Rak, Barbara (Image of Non Profit Organizations - the Role and Creating, 2007)
The paper presents the role of image of non profit organizations and its influence on creation of social backing and financial support as well as work of volunteers. The public relations activities aiming inwards organization integrate members around mission and fulfilling the goals, making company firm. Whereas adaptation of public relations instruments in looking after links between organization and stakeholders creates partnership and loyalty of volunteers, donors and supporters of organizations. It serves fulfilling the social goals.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 86-96